Soil moisture conservation in water-deficit hill agriculture: Affordable to small landholdings - Choudhury, Burhan U (Indian Farming, 2023)
Rain-fed agriculture in the hills of north-eastern India is at the risk of crop failure, primarily due to over-dependence on inconsistent distribution and variable intensity of rainfall. Intermittent long dry spell between monsoon months (June–September) delay the timely planting of summer crops. In the rainless (<200 mm annually) months (November–March), moisture stress in sloping upland restricts rabi (winter) cultivation to <20% of kharif (rainy) area (4.24 million ha). Adopting soil water conservation practices (SWCPs) in situ or ex situ may benefit to address these constraints. The recommended SWCPs such as watershed engineering and mechanical measures are skilloriented, expensive and difficult to implement and maintain on marginal/small hilly farms. This article proposes some of the simplest yet cost-effective and affordable SWCPs to mitigate moisture stress while expanding rabi agriculture and improving existing low cropping intensity ( 120%) for food and nutritional security in the region.